Pengaruh Keragaman Gula Aren Cetak Terhadap Kualitas Gula Aren Kristal (Palm Sugar) Produksi Agroindustri Kecil - susi susi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
Cyrstal palm sugar was one product diversification of palm sugar that utilization continues to grow and is expected to reduce its dependence on white sugar. Crystal palm sugar can be processed from the sap of palm or palm sugar product which melted. Utilization palm sugar as a raw material is one way to reduce excess palm sugar, but on the other hand is rather difficult to control the quality of raw materials. Wide variations in the quality of the palm sugar will also cause the palm sugar crystal products are diverse as well. Palm sugar produced by different producer will produce different quality. This research was conducted how difference between the quality of raw materials and their effects on quality crystal palm sugar. This study showed that some producer producing different quality and this affects the quality of palm sugar crystals obtained. Average moisture content, ash content and insoluble solids content in raw material palm sugar were 12.82%, 12.82%, 12:13% and 3.70%, while the products of palm sugar crystals were 6.33%, 0.24% and 5.06%. Quality criteria of crystal palm sugar that are still beyond the SNI standard where the standard maximum moisture content of 3% and insoluble solids content should be a maximum of 1%.